Bilateral taste disorders in patients with Ramsay Hunt syndrome and Bell palsy. Issue 4 (10th April 2018) - Pavlidis, Pavlos; Cámara, Rafael J. A.; Kekes, Georgios; Gouveris, Haralampos
Abstract : Objective: Ramsay Hunt syndrome (RHS) and Bell palsy (BP) are typically known as facial nerve motor syndromes and are primarily unilateral. The aim of this study was to challenge this assertion, because both conditions are also known to be associated with viruses that typically affect several nerves. Methods: Ten participants with RHS, 12 with BP, all clinically unilateral, and 12 healthy controls were prospectively enrolled. Electrogustometric thresholds were measured bilaterally in the areas of the chorda tympani, the glossopharyngeal, and the major petrosal nerve. Also bilaterally, the taste function was tested using chemogustometry with different tastant concentrations. Again bilaterally, the morphology of the mucosa and the vessels of the anterior fungiform papillae were examined by contact endoscopy. Statistically, RHS and BP participants were compared with the healthy controls, and the paretic sides of RHS and BP were compared pairwise with their mobile sides. Results: Electrogustometrically, perception was reduced bilaterally in RHS (10–19dB, p < 0.001) and BP (3–5dB, p = 0.011–0.030) in all 3 innervation areas. Chemogustometrically, it was also reduced bilaterally in RHS (20–70%) and BP (8–50%). Papillary atrophies were increased 100% in RHS ( p = 0.001) and BP ( p < 0.001). They were more increased on the paretic side in RHS (30%, p = 0.078) and BP (83%, p < 0.001). Interpretation: In these 2 clinically unilateral conditions, the gustatory perception and morphology are bilaterally affected, more in RHS and more on the paretic side. BP, known as an isolated motor condition, appears to be a cranial polyneuritis. A bilateral examination and therapeutic gustatory monitoring might follow these observations in evidence‐based practice. Ann Neurol 2018;83:807–815